Transnationalism, diaspora, and development: A purposive review of the literature. Issue 12 (19th October 2018) - Tan, Yan; Liu, Xuchun; Rosser, Andrew; Yeoh, Brenda; Guo, Fei
Abstract: In view of the observation of some scholars and policymakers that contemporary international migration and its developmental effects are better understood from a transnational perspective, this paper attempts a systematic review of the impact of the transnational perspective on the relationship between migration and development in the fields of migration studies, population studies, and demography. Based on a study of 666 publications on transnationalism, diaspora, and development derived using keyword searches of the Web of Science database and a more in‐depth review of a subset of 60 influential papers on transnational linkages, the paper discusses five types of transnational linkages—familial, political, economic, sociocultural, and subjective. While the influence of transnationalism has been profound, stimulating an innovative body of work on changing migration patterns, the linkages between diaspora and their homelands, and the impact of these linkages on development, the review also identified significant gaps, namely, the inadequate attention to generating evidence of the developmental impact of transnational migration, particular in the Global South; the lack of consideration for the way diaspora from single homelands is internally differentiated and distributed across multiple transnational social spaces; and the need to identify data sources for more robust quantitative analyses of the multiple linkages between diaspora and development.